Mapping the Teachers’ Learning and Development Needs within the National Competency-Based Teacher Standards (NCBTS) Framework Towards Achieving Quality Education for All - Eunice Mareth Querol Areola, PhD HSG; Pearliza Domalaon (Journal of Sustainable Community Development (JSCD), 2026)
As a contribution to attaining quality education, this study examined the competencies of Basic Education teachers employed in a private academic institution in Quezon City that follows a non-traditional approach to learning. Teacher competencies were evaluated using the National Competency-Based Teacher Standards (NCBTS) across seven domains: social regard for learning, learning environment, diversity of learners, curriculum, planning, assessing and reporting, community linkages, and personal growth and professional development. Findings revealed that teachers generally rated themselves as highly competent in five of the seven domains, indicating strengths that support their effectiveness as educators and alignment with national standards. Moderate ratings were observed in the domains of diversity of learners and planning and assessment, highlighting priority areas for professional development, particularly within a non-traditional academic setting. Based on these findings, teachers’ learning and development needs were assessed and mapped to inform a sustained faculty development plan aimed at enhancing professional competence and teaching effectiveness.